Investigating innovative technique for managing Failure Modes and Effects Analysis - Alruqi, Mansoor (2021)
The investigation of failures and their prevention throughout a design process forms an effective approach that can reduce such occurrences during manufacturing. To address this issue, Failure Modes and Effects Analysis (FMEA) was developed as a methodology to proactively evaluate the potential failures in a product, process or service. In the context of the product development process, FMEA is employed in three distinct areas, labelled: (1) Functional FMEA – looking at the potential failures associated with product and system functions, (2) Design FMEA – considering the potential failures identified in the product sub-system functions and component designs and (3) Process FMEA – evaluating the potential failures found in manufacturing and assembly processes.